Discrete Fractional Solutions of a Gauss Equation - Yilmazer, Resat; Demirel, Neslihan Sabriye (Amer Inst Physics, 2018)
One of the most popular research interests of science and engineering is the fractional calculus theory in recent times. Discrete fractional calculus has also an important position in fractional calculus. In this work, we acquire some new explicit solutions of the Gauss differential equation by using discrete fractional nabla operator. The most important advantage of the method is that it can be applied for singular equations.
7th International Eurasian Conference on Mathematical Sciences and Applications (IECMSA) -- AUG 28-31, 2018 -- Kyiv, UKRAINE
Keywords: Calculus Operator